RETRACTED: Ecological approaches to the formation of sustainable rural development - Nechaeva Marina; Kuklin Andrey; Demidova Elena; Mottaeva Asiiat; Pryadko Igor (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001